R-matrix method and the nonlocal nucleon optical potential - Loan, Doan Thi; Phuc, Nguyen Hoang; Khoa, Dao Tien (Communications in Physics, 2018)
The calculable R-matrix method is applied to solve the Schr ̈odinger equationin the optical model (OM) analysis of the elastic nucleon-nucleus scatter-ing using a nonlocal nucleon optical potential (OP). The phenomenologicalnonlocal nucleon OP proposed by Perey and Buck (PB), and the two recentversions of the PB parametrization were used in the present OM study of theelastic nucleon scattering on 208 Pb and 27 Al targets at different energies. Thecomparison of the OM results given by the calculable R-matrix method withthose given by other methods confirms that the calculable R-matrix methodis an efficient tool for the OM study of the elastic nucleon-nucleus scatteringusing a nonlocal nucleon OP.